“A tropical paradise”. Jamaica in National Geographic (Tzintzun, Revista de Estudios Históricos, 2016)
This paper examines the visual and narrative discourse as a representationbuilt through articles and photographs publishedin National Geographic on the island of Jamaica. It highlights thestrategies and the various tropes, stereotypes, and repetition thathelped create an image of the island territory and its populationover several decades of the twentieth century.
Keywords: National Geographic; Jamaica; Caribbean; tourism; visual discourse; narrative discourse; representations